2012
DOI: 10.1371/journal.pone.0036789
|View full text |Cite
|
Sign up to set email alerts
|

The BMP Ligand Gdf6 Prevents Differentiation of Coronal Suture Mesenchyme in Early Cranial Development

Abstract: Growth Differentiation Factor-6 (Gdf6) is a member of the Bone Morphogenetic Protein (BMP) family of secreted signaling molecules. Previous studies have shown that Gdf6 plays a role in formation of a diverse subset of skeletal joints. In mice, loss of Gdf6 results in fusion of the coronal suture, the intramembranous joint that separates the frontal and parietal bones. Although the role of GDFs in the development of cartilaginous limb joints has been studied, limb joints are developmentally quite distinct from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Previous studies show that GDF6 can promote chondrogenesis (Erlacher et al, 1998; Gooch et al, 2002; Nochi et al, 2004), but can also act as inhibitor of osteogenesis (Shen et al, 2009; Clendenning et al, 2012). Digit bones form from cartilaginous precursors, and smaller toes in Gdf6 mutants likely reflects reduced chondrogenic activity in developing footplates, similar to the shortening of endochondral bones seen with mutations in other closely related GDF signaling molecules (Storm et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that GDF6 can promote chondrogenesis (Erlacher et al, 1998; Gooch et al, 2002; Nochi et al, 2004), but can also act as inhibitor of osteogenesis (Shen et al, 2009; Clendenning et al, 2012). Digit bones form from cartilaginous precursors, and smaller toes in Gdf6 mutants likely reflects reduced chondrogenic activity in developing footplates, similar to the shortening of endochondral bones seen with mutations in other closely related GDF signaling molecules (Storm et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…GDF6 also acts during embryogenesis to regulate cell differentiation. In the mouse, Gdf6 inhibits differentiation of the mesenchymal progenitors that develop into the coronal suture, and precocious differentiation of these cells results in fusion (60,61). Thus, in certain tissues, GDF6 can promote cell survival during development as well as regulate terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the BMP2 -related intracellular osteogenic cascade is activated in calvarial cells isolated from prematurely fused sutures of affected individuals [Lattanzi et al, 2013]. The importance of the BMP pathway in the pathogenesis of CS is further corroborated by studies of animal models: BMP3 variants are found in brachycephalic dog breeds [Schoenebeck et al, 2012], mice with loss of BMP13 (also known as growth differentiation factor 6, Gdf6 ,) have coronal CS [Clendenning and Mortlock, 2012], while metopic CS is observed in mice with enhanced BMP signaling through constitutive activation of bmp receptor, type 1A ( Bmpr1a ) expression in cranial neural crest-derived structures [Komatsu et al, 2013]. In these models, craniosynostosis is believed to originate from an upregulation of Smad-dependent BMP signaling in the neural crest, resulting in enhanced ossification of the derived cranial bones [Komatsu et al, 2013].…”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%